Eksperimen Pembelajaran Matematika dengan Strategi Explicit Instruction dan Discovery Learning Terhadap Hasil Belajar Matematika Ditinjau dari Konsentrasi Belajar Siswa Kelas VII SMP Batik Surakarta Tahun 2016/2017 - Adinata, Yuda Candri; , Prof.Dr. Sutama, M.Pd (2017)
Education has a central role in building and advancing a nation. Implementation of education should lead students into personal focus in developing our potential. Math requires optimal concentration in the learning process, so it is considered as a subject that is difficult, to understand by students. Learning strategies used by teachers to be varied, so interesting in the learning process. . This study aims to describe and analyze: (1) Test the effect explicit instruction strategy and discovery learning on learning outcomes in mathematics, (2) Test the effect learning concentration on learning outcomes in mathematics, (3) Test the interaction explicit instruction strategy and discovery learning and learning concentration on learning outcomes in mathematics. The research was conducted students of VII Grade of SMP Batik Surakarta odd semester of academic year 2016/2017 with the population all students of VII a number of 302 students. Type of the research is experiment with quasi experimental design. The class sample of research by using the strastified cluster random sampling. Methods of data collection use test, questionnaire, and documentation. Data analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) There is effect explicit instruction strategy and discovery learning on learning outcomes in mathematics, (2) There is effects learning concentration on learning outcomes in mathematics, (3) There is no interaction explicit instruction strategy and discovery learning and learning concentration on learning outcomes in mathematics. Keywords: explicit instruction, discovery learning, learning concentration, learning outcomes in mathematics